The Transformation of Balaghah Theory in the Tradition of Qur’anic Interpretation - Teguh Arafah; Irfan Jaya Sakti; Muhammad Hidayat (Al-'Allāmah: Journal of Scriptures and Ulama Studies, 2025)
Balaghah science is a discipline of Arabic language that plays an important role in the interpretation of the Qur'an in order to reveal the greatness of the grammar of the Qur'an. This science also plays a role for someone to know and understand how to communicate using beautiful, effective, targeted language and situations. This article attempts to reveal the phases of the development of balaghah science, reveal the relationship between the taste of the language of the Qur'an and its relationship to balaghah science, and the role of balaghah science in classical and contemporary interpretations. This article uses a bibliography writing methodology using descriptive and scientific analysis methods. The results of this study indicate that balaghah science has been inherent in the culture of the Arab Jahiliyah nation, as well as after the revelation of the Qur'an so that scholars classified it into three major themes in this study; bayan science, badi' science and maani science. The existence of the science of balaghah as a response to the beauty of the language of the Qur'an so that the theories in the science of balaghah known as kinayah, isti'arah, majaz mursal and other theories are applied in revealing the beauty of the taste of the verses of the Qur'an, so that the balaghah of the Qur'an reveals the Secret of the Qur'an which is very abundant, while human capabilities are very limited.